Genome wide binding site analysis reveals transcriptional coactivation of cytokinin-responsive genes by DELLA proteins - Marín- de la Rosa, Nora; Pfeiffer, Anne; Lohmann, Jan U. (PLoS Genetics, 2015)
Author Summary Plants respond to environmental cues by modulating transcriptional circuits. One mechanism for such modulation involves DELLA proteins. They are promiscuous interactors of transcription factors and, in most cases, this interaction impairs the recognition of the DNA target sequences. Here we show that DELLA proteins are also recruited to multiple locations of the genome where they act as transcriptional coactivators, and we demonstrate how physical interaction with type-B ARRs is relevant for the regulation of meristem maintenance and photomorphogenesis.
Gesehen am 19.06.2017